Boron-Doped Diamond/GaN Heterojunction—The Influence of the Low-Temperature Deposition - Michał Sobaszek (MDPI AG, 2021)
We report a method of growing a boron-doped diamond film by plasma-assisted chemical vapour deposition utilizing a pre-treatment of GaN substrate to give a high density of nucleation. CVD diamond was deposited on GaN substrate grown epitaxially via the molecular-beam epitaxy process. To obtain a continuous diamond film with the presence of well-developed grains, the GaN substrates are exposed to hydrogen plasma prior to deposition. The diamond/GaN heterojunction was deposited in methane ratio, chamber pressure, temperature, and microwave power at 1%, 50 Torr, 500 °C, and 1100 W, respectively. Two samples with different doping were prepared 2000 ppm and 7000 [B/C] in the gas phase. SEM and AFM analyses revealed the presence of well-developed grains with an average size of 100 nm. The epitaxial GaN substrate-induced preferential formation of (111)-facetted diamond was revealed by AFM and XRD. After the deposition process, the signal of the GaN substrate is still visible in Raman spectroscopy (showing three main GaN bands located at 565, 640 and 735 cm−1) as well as in typical XRD patterns. Analysis of the current–voltage characteristics as a function of temperature yielded activation energy equal to 93.8 meV.